Comprensión lectora en contexto de post pandemia en estudiantes de segundo y cuarto grado de primaria en la Institución Educativa Agustín Rivas Vásquez, distrito de Fernando Lores 2025 - Arévalo Cortegano, Tomy Franco (2025)
The main objective of this research was to determine the level of reading comprehension in a post-pandemic context among 2nd and 4th grade primary school students at Agustín Rivas Vásquez School, located in the district of Fernando Lores, in the year 2025. The methodology employed was a quantitative approach, considered invariant as it deciphers or estimates parameters within the informant units. The research design was descriptive and field-based. The study involved a sample of 110 students from 2nd and 4th grade of primary education. For data collection, a development test validated by experts was used as the main instrument. The findings revealed that post-pandemic reading comprehension—at the literal, inferential, and critical levels—among 2nd and 4th grade students at Agustín Rivas Vásquez School in 2025 was predominantly at the "beginning" level. Specifically, 70.9% of students were at the "beginning" level overall. Regarding literal comprehension, 48.2% of students were at the "beginning" level. For inferential comprehension, 66.4% of 2nd grade students were classified at the "beginning" level. Finally, in terms of critical comprehension, 75.5% of 2nd and 4th grade students were also at the "beginning" level.